(3GdTPQGJ GdEdgjI aj Ydhe GdMbGFb GdQHGfjIs - (3eMeO Hf eMehO GdETQGbj GdTgQRhQj , TeS GdOjf,J (B687 (3g` s ((3SYO GdOjf Hf YHO Gddg Hf eMeO GdMajXi GdSjhai s)
(3ChdgG (B:s
(3ebGegeG daX eaQO cbhdc GdMjhGf GdfGWb aEf GdMjhGf GdfGWb s
(3BNQgG (B:s
(3fLR GdcJGHq s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs